Repeated Activation of a CS-US-Contingency Memory Results in Sustained Conditioned Responding - Joos, Els; Vansteenwegen, Debora; Vervliet, Bram; Hermans, Dirk (Frontiers in Psychology, 2013)
Individuals seem to differ in conditionability, i.e., the ease by which the contingent presentation of two stimuli will lead to a conditioned response. In contemporary learning theory, individual differences in the etiology and maintenance of anxiety disorders are, among others, explained by individual differences in temperamental variables (Mineka & Zinbarg, 2006). One such individual difference variable is how people process a learning experience when the conditioning stimuli are no longer present. Repeatedly thinking about the conditioning experience, as in worry or rumination, might prolong the initial (fear) reactions and as such, might leave certain individuals more vulnerable to developing an anxiety disorder. However, in human conditioning research, relatively little attention has been devoted to the processing of a memory trace after its initial acquisition, despite its potential influences on subsequent performance. Post-acquisition processing can be induced by mental reiteration of a CS-US-contingency. Using a human conditioned suppression paradigm, we investigated the effect of repeated activations of a CS-US-contingency memory on the level of conditioned responding at a later test. Results of three experiments showed more sustained responding to a ‘rehearsed’ CS+ as compared to a ‘non-rehearsed’ CS+. Moreover, the second experiment showed no effect of rehearsal when only the CS was rehearsed instead of the CS-US-contingency. The third experiment demonstrated that mental CS-US-rehearsal has the same effect regardless of whether it was cued by the CS and a verbal reference to the US or by a neutral signal, making the rehearsal ‘purely mental’. In sum, it was demonstrated that post-acquisition activation of a CS-US-contingency memory can impact conditioned responding, underlining the importance of post-acquisition processes in conditioning. This might indicate that individuals who are more prone to mentally rehearse information condition more easily.